Effects of prescribed burning on understory Quercus species of Pinus yunnanensis forest - Hong, Ruicheng; Li, Jialin; Wang, Jin; Zhu, Xilong; Li, Xiaona; Ma, Cheng; Cao, Hengmao; Wang, Leiguang; Wang, Qiuhua (Frontiers in Forests and Global Change, 2023)
Positioning studies on prescribed burning in Pinus yunnanensis forests have been conducted for several years, focusing on the effects of fire on the composition and structure, growth, regeneration, relative bark thickness, and bark density of understory oak species in Pinus yunnanensis forests. The study was conducted on Zhaobi Mountain, Yi-Dai Autonomous County of Xinping, Yuxi City, Yunnan Province. Thirty sample plots of 10m x 10m each was established in areas where prescribed burning had been resumed for one year and where prescribed burning had not been implemented. Each plant was surveyed, and all data were compared, counted, and analyzed. The study results showed that (1) prescribed burning significantly affected the species composition of the understorey of Pinus yunnanensis forests. In both tree and shrub layers, the important values of Q. aliena, Q. serrata, Q. fabri, and Q. variabilis were significantly reduced in the burned areas. In contrast, the important values of Q. acutissima increased somewhat. (2) The under crown height of oak trees in the burned areas was significantly lower than in the burned areas, but the height of oak trees in the burned areas was not significantly different from that in the burned areas. In the shrub layer, the height and cover of oak plants in the prescribed burning areas were significantly lower than in the unprescribed burned areas, effectively reducing the vertical continuity of the forest surface combustible material and reducing the possibility of fire converting from surface to canopy fire along the "ladder fuel". (3) The regeneration of oak plants in the burned area is mainly by sprout tillers, and very few seedlings are regenerated by seed germination. Renewed seedlings are difficult to survive the prescribed burn areas the following year due to their lack of fire tolerance. (4) The relative bark thickness and density of oak plants in prescribed burn areas were significantly higher than those in unprescribed burn areas due to the fire tolerance exhibited by oak plants in long-term prescribed burns. The study results can provide a scientific basis for prescribed burning, forest fuels, and forest fire management.